(untitled) (GEOMATE Journal, 2025)
Lebanon’s complex tectonic setting has historically caused earthquakes exceeding magnitude 7. Beirut metropolis, Lebanon’s economic center, is particularly exposed to seismic hazard due to its proximity to active faults and diverse lithological formations. The subsoil characteristics lead to high ground motion spatial variability with significant seismic amplification. Traditional 1D and 2D models are insufficient to capture the complex effects of bedrock topography, sediment layers, and seismic wave propagation, making the development of a 3D model necessary. In this study, we developed the first simplified 3D subsurface model of Greater Beirut, incorporating data from approximately 500 geotechnical boreholes, 700 H/V spectral ratio measurements, and existing geological studies. The model reveals significant variations in Quaternary sediment thickness, with deposits exceeding 70 meters in the Borj Hammoud area and outcropping rocks in Ras Beirut and Achrafieh. Shear wave velocity averages 300 m/s, enabling the estimation of fundamental resonance frequencies, which range from 0.5 Hz in deep basins to over 10 Hz in rocky zones. By addressing data gaps in southern Beirut using advanced interpolation and machine learning techniques, this model establishes a foundation for future numerical simulations, aiding in seismic hazard assessment and urban planning.